2002
DOI: 10.1046/j.0003-2409.2001.02453.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of photoplethysmographic signals for the determination of splanchnic oxygen saturation in humans

Abstract: SummaryThe need for a clinically applicable method of detecting splanchnic hypoxia has led to experimental animal studies which indicated the usefulness of intestinal pulse oximetry. Pulse oximetry relies on detection of photoplethysmographic signals. Before developing a pulse oximeter for the measurement of organ oxygen saturation peri-operatively, we designed a system based on a re¯ectance photoplethysmographic probe to investigate photoplethysmographic signals from human viscera (bowel, liver, and kidney). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 6 publications
0
33
0
Order By: Relevance
“…Currently, there is no widely accepted and readily available monitoring technique to assess splanchnic perfusion [5]. Polarographic oxygen electrodes have been used to monitor splanchnic tissue oxygenation, but predominately remain as research tools [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is no widely accepted and readily available monitoring technique to assess splanchnic perfusion [5]. Polarographic oxygen electrodes have been used to monitor splanchnic tissue oxygenation, but predominately remain as research tools [1].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in animals have found it to be a rapid, reproducible, as well as a highly sensitive and specific technique for detecting small bowel ischemia [10]. More recently an electro-optical pulse oximetry sensor has been used for the first time in humans to measure photoplethysmographic (PPG) signals from various abdominal organs [5]. However, none of these sensors are suitable for prolonged monitoring in the abdomen.…”
Section: Introductionmentioning
confidence: 99%
“…The esophageal pulse oximeter has also been used to investigate PPG signals in the human bowel [11]. In many critically ill patients, poor tissue oxygenation is due to disordered regional distribution of blood flow, despite high global blood flow and oxygen delivery.…”
Section: Use Of the Esophageal Probe To Record Photoplethysmographic mentioning
confidence: 99%
“…PLANCHNIC organs are particularly vulnerable to hypoperfusion [1]. If an organ or tissue is not sufficiently perfused with oxygenated blood, cell death and tissue necrosis can ensue.…”
Section: Introductionmentioning
confidence: 99%